Solid‐State NMR Spectroscopy Proves the Presence of Penta‐coordinated Sc Sites in MIL‐100(Sc). Issue 40 (24th May 2017) - Giovine, Raynald; Volkringer, Christophe; Ashbrook, Sharon E.; Trébosc, Julien; McKay, David; Loiseau, Thierry; Amoureux, Jean‐Paul; Lafon, Olivier; Pourpoint, Frédérique
Abstract: Advanced solid‐state NMR methods and first‐principles calculations demonstrate for the first time the formation of penta‐coordinated scandium sites. These coordinatively unsaturated sites were shown during the thermal activation of scandium‐based metal‐organic frameworks (MOFs). A 45 Sc NMR experiment allows their specific observation in activated Sc3 BTB2 (H3 BTB=1, 3, 5‐tris(4‐carboxyphenyl)benzene) and MIL‐100(Sc) MOFs. The assignment of the ScO5 groups is supported by the DFT calculations of NMR parameters. The presence of ScO5 Lewis acid sites in MIL‐100(Sc) explains furthermore its catalytic activity. The first NMR experiment to probe 13 C− 45 Sc distances is also introduced. This advanced solid‐state NMR pulse sequence allows the demonstration of the shrinkage of the MIL‐100(Sc) network when the activation temperature is raised. Abstract : MOF sites : Advanced solid‐state NMR methods and first‐principles calculations demonstrate for the first time the formation of penta‐coordinated scandium sites. A 45 Sc NMR experiment allows their specific observation in activated Sc3 BTB2 and MIL‐100(Sc) MOFs. The assignment of the ScO5 groups is supported by the DFT calculations of NMR parameters.